PSYCHIC SOVEREIGNTIES AND ALIEN AFFILIATIONS: POWER AND RESISTANCE IN BUTLER AND OKORAFOR’S SPECULATIVE WORLDS - Patil, Ashwin Milind; S. D. Palwekar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article examines the intricate interplay of psychic sovereignty and alien affiliation in the speculative fiction of Octavia Butler and Nnedi Okorafor, specifically analyzing Mind of My Mind, Bloodchild, and Lagoon. This study examines the reconfiguration of power and resistance beyond anthropocentric paradigms, uncovering intricate negotiations among autonomy, control, and relationality. Butler’s telepathic constructs and alien-human symbioses challenge traditional notions of individual agency, while Okorafor’s extraterrestrial interventions foreground Afrocentric paradigms of collective transformation and ecological harmony. This research posits that the examination of the intersections among psychic networks, corporeal transgressions, and postcolonial alien encounters reveals that both authors provide radical speculative frameworks for resisting domination and redefining identity. The article ultimately situates Butler and Okorafor’s works as significant contributions to the discourse of speculative resistance, wherein the alien and the psychic emerge as realms of liberation, hybridity, and reimagined futures.